2011
DOI: 10.1162/evco_a_00035
|View full text |Cite
|
Sign up to set email alerts
|

Representations and Evolutionary Operators for the Scheduling of Pump Operations in Water Distribution Networks

Abstract: Reducing the energy consumption of water distribution networks has never had more significance. The greatest energy savings can be obtained by carefully scheduling the operations of pumps. Schedules can be defined either implicitly, in terms of other elements of the network such as tank levels; or explicitly, by specifying the time during which each pump is on/off. The traditional representation of explicit schedules is a string of binary values with each bit representing pump on/off status during a particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… To reduce the search space, decision variables are combined applying relative time control triggers (Lopez-Ibanez et al 2011).  Time horizon is 24 hours divided into 1-hour intervals.…”
Section: Hashemi Et Al (2014) Somentioning
confidence: 99%
“… To reduce the search space, decision variables are combined applying relative time control triggers (Lopez-Ibanez et al 2011).  Time horizon is 24 hours divided into 1-hour intervals.…”
Section: Hashemi Et Al (2014) Somentioning
confidence: 99%
“…It has been shown that integration of domain knowledge as an element of the evolutionary process is beneficial [19], [20]. For example, [21] demonstrated the benefits of incorporating semantic attributes of the problem domain into the representation framework when designing networks for water distribution. Similarly, in [22], an N -dimensional pixel was used as the key element to represent solutions in a shapeoptimisation problem; demonstrating that a representation that emulates the real-world morphology obtains better results than a more generic "traditional" representation.…”
Section: Introductionmentioning
confidence: 99%
“…To define pump schedules, binary encoding is most commonly adopted, where only fixed-speed pumps are involved in the network and their on/off states across different time intervals can thus be represented by several binary bits. Alternatively, time-controlled triggers [ 14 , 15 ] can also be used, where the active and inactive periods of time intervals resulting from every pump switch are successively coded in an individual solution. On the other hand, real-value encoding is used to directly define the actuator's continuous states for water networks where only variable-speed pumps are involved, though this has attracted significantly less research.…”
Section: Introductionmentioning
confidence: 99%